STRATEGI KOMUNIKASI PEMASARAN DALAM KEGIATAN PEMASARAN PRODUK CONSUMER GOODS (STUDI KASUS PADA PT EXPAND BERLIAN MULIA DI SEMARANG) - Indah Sri Wahyuni (Kompetensi (Competence : Journal of Management Studies), 2017)
Marketing communication is a form comunication that aims to strengthen the marketing strategy and comunucation alications to help the marketing activities of a company. In addition, the marketing comunication activites are intended to introduce, establish and create interactions between companies with business partners and customers, and is an attempt to communicate the company, the products or services to outside business partners, suppliers and consumers. Marketing communication strategies in consumer goods marketing should be able to achieve the goal of marketing, that is satisfy the customers.This study wanted to know how the marketing communication strategies in marketing consumer goods in the PT Expand Berlian Mulia Semarang. The object of this study conducted to assess the marketing communication strategies in marketing consumer goods in PT Expand Berlian Mulia  Semarang. The study subject is PT Expand Berlian Mulia Semarang and chose this company because of its position as a market leader in the field of consumer goods distributor. The theories used in this research are the process of communication, strategy, marketing communication strategies SOSTAC models, and forms of marketing or promotional communications. The paradigm of this research is construktivist  paradigm and research method used the case study method of qualitative approaches. This study tried to find empirical evidence of the object research,reveals how marketing communication strategies in consumer goods marketing products at PT Expand Berlian Mulia and develop the meaning of the implementation of marketing communication activities. Results showed correspondence between conceptual patterns predicted by theories that are relevant to the empirical findings patterns of case studies. Based on the analysis conducted can be concluded that marketing communication strategies in PT Expand Berlian Mulia use promotion mix such asadvertising, sales promotion, personal selling and marketing events. Marketing communication activities are supported by the company's brand or principal holder